Remodelação óssea com as forças contínua, contínua interrompida e intermitente: movimentação dentária induzida em ratos - Micheletti, Kelly Regina [UNESP] (2015)
Introduction: There are few researches about the behavior of the alveolar bone in relationship of three different types of forces. Objective: To evaluate if the bone on the contralateral side to orthodontic tooth movement can be used as the control group (CL) and the amount of bone tissue during the application of different types of force in rats molars. Methods: 60 male rats (Rattus norvegicus Wistar), with approximately 90 days of age and weight of 300g, divided into 4 groups according to the type of force: control group (C), continuous force (CF), intermittent continuous force (ICF) and interrupted force (IF); The groups were distributed in periods of 5, 7 and 9 days (n = 6). Were analyzed the amount of bone tissue of right upper first molar. The evaluation were conducted with Anova and Tukey's tests a significance level of 5% (p <0.05). Results: The collagen analysis demonstrated a statistically significant difference between the C group (80 ± 0.01%) and CF (62.2 ± 0.15%), whereas no significant differences were found between the CL group and the other groups. Immunolabeling for OPG was similar in the C and CL groups. RANKL on the mesial face was similar in the CL and CF group. However, significant differences were found between the CL group and the other groups on the distal face, whereas no significant difference on the distal face was found between the C and CF group. The intergroup bone tissue analysis showed that the five days of induced tooth movement (ITM) was no significant decrease in bone percentage of CF groups (62% ± 0.14), ICF (55% ± 0.07) and IF (54% ± 0, 05) in the C group (0.01 ± 80%) (p <0.05). At 7 days of ITM, this reduction was still significant in the CF group (64% ± 0.1) and IF (38% ± 0.1) compared to C group (80% ± 0.01) and there was also difference statistically significant between CF (64 ± 0.1%) and IF (38% ± 0.1)...